Requirements to the tactile Internet and approaches for implementation - Simeonova, Tsvetelina (Yearbook Telecommunications, 2022)
The aim of this paper is to outline the specifics of network service parameters, as well as the basic technical requirements for the tactile Internet based on mobile networks, which are the basis for developing its system and functional architecture, components and interactions in architecture. The accepted interfaces in the tactile Internet network are given and an analysis of protocols proposed for use for tactile Internet is made. The results are related to the differentiation of the features of architecture, interfaces and protocols of the tactile Internet. Contributions from the work are the comprehensive consideration and analysis of the development of the tactile Internet, outlining some possible current directions of research, as well as existing highlights and open questions.